(untitled) (Research, Society and Development, 2022)
Introduction: Nutritional guidance aimed at the preparation of athletes is essential for there to be a balance of energy and nutrients, in this context supplementation emerges as a nutrient replacement mechanism that maintains, through formulas that are not harmful to the human body, the energy necessary for the practice of exercise. Objective: Expose about the importance of the nutritionist in the construction of an adequate nutritional profile for athletes. Methodology: The method of integrative literature review was applied, with a qualitative approach, where 10 articles published between the years 2015-2022 were analyzed. Through the search descriptors in the databases: Google Scholar, Lilacs and Scielo. Results and Discussion: Nutritional guidance was highlighted as a basic area for the athlete because the misuse of supplements can harm health and impair physical performance in athletes. In this sense, the prescription of supplements by a nutritionist should be based on an assessment of the athlete’s nutritional status, food planning, adjustments in food consumption and a clear duration of supplement use. Conclusion: The results of the analysis can conclude that in addition to meeting their energy needs, most athletes use food supplements to improve their performance on the field. However, it is clear how important the role of the nutritionist is for the athlete to follow the correct indications, using only essential and short-term food supplements without harming their health.